Revenue prediction for integrated renewable energy and energy storage system using machine learning techniques. (June 2022) - Lin, Yingqian; Li, Binghui; Moiser, Thomas M.; Griffel, L. Michael; Mahalik, Matthew R.; Kwon, Jonghwan; Alam, S. M. Shafiul
Highlights: We present an innovative method for predicting revenue of hydropower hybrid systems. The empirical method enables prediction based on easily accessible inputs. The method reduces more than 99% computation time compared to conventional method. The average absolute revenue prediction error is 4%. The method is applicable to any hydropower plant in a competitive electricity market. Abstract: Revenue estimation for integrated renewable energy and energy storage systems is important to support plant owners or operators' decisions in battery sizing selection that leads to maximized financial performances. A common approach to optimizing revenues of a hybrid hydro and energy storage system is using mixed-integer linear programming (MILP). Although MILP models can provide accurate production cost estimations, they are typically very computationally expensive. To provide a fast yet accurate first-step information to hydropower plant owners or operators who consider integrating energy storage systems, we propose an innovative approach to predicting optimal revenues of an integrated energy generation and storage system. In this study, we examined the performance of two prediction techniques: Generalized Additive Models (GAMs) and machine learning (ML) models developed based on artificial neural networks (ANN). Predictive equations and models are generated based on optimized solutions from a market participation optimization model, the Conventional Hydropower Energy and Environmental Resource System (CHEERS) model. The two predicting techniques reduce the computational time to evaluate annual revenue for one set of battery configurations from 3 h to 1 to 4 min per run while also being implementable with significantly less data. The model validation prediction errors of developed GAMs and ML models are generally below 5%; for model testing predictions, the ML models consistently outperform the regression equations in terms of root mean square errors. This new approach allows plant owners, operators, or potential investors to quickly access multiple battery configurations under different energy generation and market scenarios. This new revenue prediction method will therefore help reduce the barriers, and thereby promoting the deployment of battery hybridization with existing renewable energy sources.